Child and adolescent psychiatry patients coming of age: a retrospective longitudinal study of inpatient treatment in Tyrol. Issue 1 (December 2016) - Fuchs, Martin; Kemmler, Georg; Steiner, Hans; Marksteiner, Josef; Haring, Christian; Miller, Carl; Hausmann, Armand; Sevecke, Kathrin
Abstract Background Mental illness is a common phenomenon at all ages. Various independent studies have shown that psychopathology is often expressed on a continuum from youth to adulthood. The aim of our study was to demonstrate a) the frequency of admission of former child and adolescent psychiatry inpatients (CAP-IP) to adult inpatient mental health facilities, and b) a potential longitudinal diagnostic shift. This is the first Austrian study designed to shed light on these issues. Methods Nearly 1000 inpatient cases at a specialized child and adolescent care center were analyzed. These cases were then tracked using data matching with registry data from adult psychiatric institutions. Overall, our observational period was 23 years. Results 26 % of our sample of former CAP-IP used psychiatric inpatient mental health services as adults, thus indicating chronicity or reoccurrence. In line with previous literature, there were patients who stayed in the same diagnostic category as well as patients with a diagnostic shift from childhood to adulthood. Conclusions Childhood and adolescence is a very important period for early intervention and prevention of mental illness. Our findings support the notion of the continuity of psychopathology from youth into adulthood.